2016
DOI: 10.1093/mnras/stw1286
|View full text |Cite
|
Sign up to set email alerts
|

The link between the assembly of the inner dark matter halo and the angular momentum evolution of galaxies in the EAGLE simulation

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
117
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(139 citation statements)
references
References 71 publications
21
117
1
Order By: Relevance
“…This parameter is usually defined as = jz/j(E), where j(E) is the maximum specific angular momentum possible for a star with specific binding energy E (Abadi et al 2003), or as V = jz/rvc(r), where vc(r) = GM (< r)/r is the circular velocity at the distance r (Scannapieco et al 2009(Scannapieco et al , 2012. Some examples of such circularity-based morphological parameters include the discto-total ratio, defined as the fraction of stars with sufficiently circular orbits, typically D/T = f ( > 0.7) ≈ f ( V > 0.8) (Aumer et al 2013;Marinacci, Pakmor & Springel 2014), or the bulge-tototal fraction, usually defined as B/T = 2 × f ( < 0) (but see Martig et al 2012;Zavala et al 2016, for an improved B/T measurement). We have found that κrot is strongly correlated with any of these alternative measures of kinematic morphology, despite the fact that κrot cannot distinguish the sense of rotation of a particle about the z-axis, i.e.…”
Section: The Amount Of Rotational Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…This parameter is usually defined as = jz/j(E), where j(E) is the maximum specific angular momentum possible for a star with specific binding energy E (Abadi et al 2003), or as V = jz/rvc(r), where vc(r) = GM (< r)/r is the circular velocity at the distance r (Scannapieco et al 2009(Scannapieco et al , 2012. Some examples of such circularity-based morphological parameters include the discto-total ratio, defined as the fraction of stars with sufficiently circular orbits, typically D/T = f ( > 0.7) ≈ f ( V > 0.8) (Aumer et al 2013;Marinacci, Pakmor & Springel 2014), or the bulge-tototal fraction, usually defined as B/T = 2 × f ( < 0) (but see Martig et al 2012;Zavala et al 2016, for an improved B/T measurement). We have found that κrot is strongly correlated with any of these alternative measures of kinematic morphology, despite the fact that κrot cannot distinguish the sense of rotation of a particle about the z-axis, i.e.…”
Section: The Amount Of Rotational Supportmentioning
confidence: 99%
“…Instead, Sales et al (2012) proposed that a disc forms when the angular momentum of freshly accreted gas is aligned with that of earlier gas accretion. Furthermore, Zavala et al (2016) found that galaxy morphology is correlated with the assembly history of the inner DM halo. In particular, they found that the 'angular momentum loss' of a galaxy's stellar component is strongly linked to that of the inner DM halo, whereas the angular momentum history of a galaxy's cold gas is statistically correlated with that of the whole DM halo.…”
Section: Introductionmentioning
confidence: 99%
“…Sales et al (2009) and Stevens et al (2016) showed that the MMW model fails to match the output of the EAGLE simulation and its ancestor OWLS. Zavala et al (2016) found the angular momentum of stars to correlate with that of the inner halo in EAGLE, and Sales et al (2012) reported weak correlation of galaxy properties with halo spin in the related GIMIC simulation. This is in contrast with other simulations in which halo spin correlates more strongly with galaxy spin and morphology, especially at low mass (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Teklu et al 2015). In particular, they are able to reproduce the parallel scaling relations of angular momentum versus stellar mass displayed by observed early-type and latetype galaxies (Zavala et al 2016). These advances open the door to detailed studies that will elucidate the nature of angular momentum evolution in a fully (hydro)dynamical cosmological context (e.g.…”
Section: Introductionmentioning
confidence: 89%
“…Second, it employs a Lagrangian analysis in a simulation based on a mesh code, using tracer particles, while previous Lagrangian analyses on this topic have all been based on Smoothed Particle Hydrodynamics (SPH) (e.g. Zavala et al 2016). …”
Section: Introductionmentioning
confidence: 99%